Subjective Experiences of Speech and Language Therapy in Patients with Parkinson's Disease: A Pilot Study. (8th July 2015) - Spurgeon, Laura; Clarke, Carl E.; Sackley, Cath
Abstract : Purpose . Parkinson's disease can produce a range of speech-language pathologies, which may require intervention. While evaluations of speech-language therapy have been undertaken, no work has been undertaken to capture patients' experiences of therapy. This was the aim of the present study. Methods . Semistructured interviews, using themes derived from the literature, were conducted with nine Parkinson's disease patients, all of whom had undergone speech-language therapy. Participants' responses were analysed in accordance with Thematic Network Analysis. Results . Four themes emerged: emotional reactions (frustration, embarrassment, lack of confidence, disappointment, and anxiety); physical impact (fatigue, breathing and swallowing, and word production); practical aspects (cost of treatment, waiting times, and the actual clinical experience); and expectations about treatment (met versus unmet). Conclusions . While many benefits of speech-language therapy were reported, several negative issues emerged which could impact adversely on rehabilitation. Parkinson's disease is associated with a range of psychological and physical sequelae, such as fatigue and depression; recognising any individual experiences which could exacerbate the existing condition and incorporating these into treatment planning may improve rehabilitation outcomes.